1992
DOI: 10.1111/j.1365-2818.1992.tb01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectroscopic study (ESI, EELS) of Nanoplast‐embedded mammalian lung

Abstract: SUMMARY The potential of Nanoplast melamine resin embedding for the study of mammalian lung parenchyma was examined by means of electron spectroscopic imaging (ESI) and electron energy‐loss spectroscopy (EELS). Samples were either fixed with glutaralde‐hyde‐paraformaldehyde or glutaraldehyde‐tannic acid, or were directly transferred to the embedding medium without prior fixation. Organic dehydrants, as well as fixatives containing heavy metals and stains, were omitted. A very high level of ultrastructural deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…Post-fixation by potassium ferrocyanide-reduced OsO 4 has been widely applied to obtain fine membrane structures with a clear contrast for morphological observation by transmission electron microscopy (Doine et al, 1984;Rambourg et al, 1993). However, we found that postfixed Tannerella forsythensis, a bacterium associated with periodontitis, followed by potassium ferrocyanidereduced OsO 4 showed no retention of immunocytochemical reactivity. It was found that 230 and 270-kDa proteins might be the component of the S-layer, based upon the results of the immunoelectron microscopic study of 4% paraformaldehyde-0.05% glutaraldehyde fixation without OsO 4 or freeze-substituted method.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…Post-fixation by potassium ferrocyanide-reduced OsO 4 has been widely applied to obtain fine membrane structures with a clear contrast for morphological observation by transmission electron microscopy (Doine et al, 1984;Rambourg et al, 1993). However, we found that postfixed Tannerella forsythensis, a bacterium associated with periodontitis, followed by potassium ferrocyanidereduced OsO 4 showed no retention of immunocytochemical reactivity. It was found that 230 and 270-kDa proteins might be the component of the S-layer, based upon the results of the immunoelectron microscopic study of 4% paraformaldehyde-0.05% glutaraldehyde fixation without OsO 4 or freeze-substituted method.…”
contrasting
confidence: 41%
“…As previously documented, ESI and EELS analyses under the EF-TEM have been applied to demonstrate isolated ferritin particles (Beckers et al, 1994), calcium elements of plant root caps (Busch et al, 1993), iodinecontaining anti-cancer drug meta-iodobenzyl guanidine (Huxham et al, 1992), P elements in mammalian lung paraenchyma (Fehrenbach et al, 1992) and cyanobacteria (Golecki and Heinrich, 1991), and calcium-ATPase in synaptic terminals (Körtje et al, 1991). These methods are fairy reliable and useful to specifically analyze several elements in biological materials and especially superior in a mapping analysis compared to an X-ray microanalysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunocytochemical localization of colloidal gold particle-conjugated secondary antibodies corresponded to the nitrogen identified by the maximal electron energy loss at 410 eV (K edge) in the ESI analysis. As reported earlier, ESI and EELS analyses under the EFTEM have been applied to demonstrate isolated ferritin particles (Beckers et al 1994), calcium elements of plant root caps (Busch et al 1993), iodine-containing anti-cancer drug meta-iodobenzyl guanidine (Huxham et al 1992), phosphorus in mammalian lung parenchyma (Fehrenbach et al 1992) and cyanobacteria (Golecki and Heinrich 1991), and calcium-ATPase in synaptic terminals (Kortje et al 1991). These methods are fairly reliable and useful for analyzing several elements in biological materials; they are especially useful for mapping analysis compared to X-ray microanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, peroxidase-DAB reaction leads to DAB polymerization via nitrogen atoms (Vannier-Santos and Lins 2001). Two different modes of the EFTEM (Golecki and Heinrich 1991, Kortje et al 1991, Fehrenbach et al 1992, Huxham et al 1992, Busch et al 1993, Beckers et al 1994) have been used for electron spectroscopic images (ESI) and electron energy-loss spectroscopy (EELS). Parallel-EELS is an additional tool.…”
mentioning
confidence: 99%